2016
DOI: 10.1097/md.0000000000005010
|View full text |Cite
|
Sign up to set email alerts
|

Transsacrococcygeal approach to ganglion impar block for treatment of chronic coccygodynia after spinal arachnoid cyst removal

Abstract: Background:Coccygodynia is a pain in the region of the coccyx that radiates to the sacral, perineal area. The cause of the pain is often unknown. Coccygodynia is diagnosed through the patient's past history, a physical examination, and dynamic radiographic study, but the injection of local anesthetics or a diagnostic nerve blockade are needed to distinguish between somatic, neuropathic, and combined pain. Ganglion impar is a single retroperitoneal structure made of both paravertebral sympathetic ganglions. Alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“…During vaginal delivery, the incidence of a sacrococcygeal ligament injury is very high and is one of the reasons for the coccygeal pain. 3 Coccyx is a delicate and mobile bone which is supported by the sacrococcygeal ligament and has more chances of sprain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During vaginal delivery, the incidence of a sacrococcygeal ligament injury is very high and is one of the reasons for the coccygeal pain. 3 Coccyx is a delicate and mobile bone which is supported by the sacrococcygeal ligament and has more chances of sprain.…”
Section: Discussionmentioning
confidence: 99%
“…Conservative management of coccydynia includes simple analgesics and use of donut shaped coccyx support for sitting on to prevent irritation of or pressure on the sacrococcygeal ligament. 3 If the pain persists or does not respond to oral analgesics then interventional procedure known as ganglion impar block is performed. However, advanced techniques include chemical neurolysis and radiofrequency ablation of the ganglion impar.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported in the literature the use of radiofrequency thermocoagulation of the ganglion impar for the treatment of chronic coccydynia with success in patients unresponsive to conservative treatment (16). And there is only one other case study that reported the use of alcohol neurolysis of the ganglion impar for the treatment of chronic coccydynia after spinal arachnoid cyst removal (17). conclusion This is a very unique case of chemical neurolysis of the ganglion impar in a patient failing multiple therapies.…”
Section: N P R E S Smentioning
confidence: 93%
“…Blocking it is useful in patients who suffer from pain in the pelvic and perineal structures as it provides nociceptive and sympathetic supply to this region [5]. The ganglion impar block is a well established procedure for the treatment of coccydynia [6], but its role in the treatment of anal pain with varied aetiologies is not well studied. In our case, the ganglion impar block hit the pain pathway's bullseye, and we were able to relieve the patient's unbearable discomfort.…”
Section: Letters To Editormentioning
confidence: 99%